2019
DOI: 10.1002/jbio.201900048
|View full text |Cite
|
Sign up to set email alerts
|

Optical sectioning and high resolution visualization of trabecular meshwork using Bessel beam assisted light sheet fluorescence microscopy

Abstract: Glaucoma, one of the leading causes of blindness, is an eye disease caused by irregularities in the ocular aqueous outflow system causing an elevated intraocular pressure. High resolution imaging of the aqueous outflow system comprising trabecular meshwork is immensely valuable to vision analysts and clinicians in comprehending the disease state for the efficacious analysis and treatment of glaucoma. Currently available ocular imaging devices are unable to deliver high resolution images for the visualization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…It is worth noting that, although utilized for single wavelength excitation, many of the LSFM systems found in the literature use semiapochromat (FLU) objectives [1, 6, 33–37]. Finally, because APO objectives are chromatically corrected for red, green, and blue colors, one may suppose that they are a good option for multicolor excitation LSFM [2, 12, 17, 23, 38–43] even when using Gaussian beams. However, the focus difference ||δCδF ranges from 2.29 to 14.29 μm, when using low NAs from 0.4 to 0.16.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that, although utilized for single wavelength excitation, many of the LSFM systems found in the literature use semiapochromat (FLU) objectives [1, 6, 33–37]. Finally, because APO objectives are chromatically corrected for red, green, and blue colors, one may suppose that they are a good option for multicolor excitation LSFM [2, 12, 17, 23, 38–43] even when using Gaussian beams. However, the focus difference ||δCδF ranges from 2.29 to 14.29 μm, when using low NAs from 0.4 to 0.16.…”
Section: Resultsmentioning
confidence: 99%
“…By sweeping the Bessel beam in x-direction to project a light sheet at each z -plane, a 3D volumetric stack can be created. 51 The sample under study should be kept stationary throughout this 3D data acquisition, which will help in minimizing motion artifacts. Such motion artefacts will be lesser in human eye imaging compared with animals under anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The Bessel beam's self-healing capability, even in a scattering environment, aids in maintaining relatively uniform illumination, resulting in improved image contrast. to the one reported in reference [59], except for the excitation objective. The use of a longerworking-distance (30 mm) apochromatic objective for exciting fluorescence from the TM provided much more flexibility during the measurements.…”
Section: Bessel Beam-based Light Sheet Fluorescence Microscopy (Lsfm)...mentioning
confidence: 91%
“…Figure 5 shows the reported sequen aging system utilizing Bessel beam-based LSFM for TM imaging [72]. Suchand Sandeep et al reported the three-dimensional (3D) visualization of the TM on an intact ex vivo porcine eye utilizing a modified version of the Bessel beam-based system [59]. The system developed had a lateral resolution of 0.78 μm and an axial resolution of 2.2 μm.…”
Section: Bessel Beam-based Light Sheet Fluorescence Microscopy (Lsfm)...mentioning
confidence: 99%